Barriers to energy efficiency improvement: Empirical evidence from small-and-medium sized enterprises in China - Genia Kostka; Ulf Moslener; Jan G. Andreas (Frankfurt School of Finance & Management, 2011)
This paper analyzes barriers for energy efficiency investments for small-and medium-sized enterprises (SMEs) in China. Based on a survey of 480 SMEs in Zhejiang Province, this study assesses financial, informational, and organizational barriers for energy efficiency investments in the SME sector. The conventional view has been that the lack of appropriate financing mechanisms particularly hinders SMEs to adopt cost-effective energy efficiency measures. As such, closing the financing gap for SMEs is seen as a prerequisite in order to promote energy efficiency in the sector. The econometric estimates of this study, however, suggest that access to information is an important determinant of investment outcomes, while this is less clear with respect to financial and organizational factors. More than 40 percent of enterprises in the sample declared that that they are not aware of energy saving equipments or practices in their respective business area, indicating that there are high transaction costs for SMEs to gather, assess, and apply information about energy saving potentials and relevant technologies. One implication is that the Chinese government may assume an active role in fostering the dissemination of energy-efficiency related information in the SME sector.
Keywords: 330; energy efficiency; SMEs; China; energy policies; information access